More than Extraction: Rethinking Data's Colonial Political Economy. Issue 2 (30th March 2023) - Gray, Catriona
Abstract: This article offers a novel conceptual framework to enable empirical investigation and analysis of the different ways in which contemporary data practices are entangled with colonialism. Departing from recent theorizations of the politics and political economy of data and data-driven technologies, including the theory of so-called data colonialism, I argue for a historicized and differentiated account of the colonial processes of dispossession at stake in datafication and the proliferation of data-dependent technologies. By undertaking a broad engagement with decolonial thinking, I demonstrate the need to move beyond an examination of how everyday life is datafied to be extracted like a natural resource. I show that such analogies are inapt and occlude colonial relations reproduced through datafication. Our understanding of these processes would find a firmer footing not in historical analogy, but in our colonial present. I propose that the modality of data's power lies not in the extraction of value as such, but in the interaction of orders of knowledge with orders of value. This reordering both acts as a motor of further colonial epistemic violence and creates the conditions for a new apparatus of racialized dispossession. Giving examples from migration governance, I set out its targets, objects, and operations.